930. HCV Treatment Is Associated With a Reduced Risk of Cardiovascular Disease Events: Results From ERCHIVES. (26th November 2018) - Butt, Adeel Ajwad; Yan, Peng; Shuaib, Ashfaq; Abou-Samra, Abdul-Badi; Saikh, Obaid; Freiberg, Matthew
Abstract: Background: Studies reporting on the association between HCV and cardiovascular disease (CVD), and effect of HCV treatment upon future risk of CVD have shown mixed results. Methods: Within ERCHIVES (Electronically Retrieved Cohort of HCV Infected Veterans), we identified all persons treated for ≥7 weeks and propensity-score-matched group who never received HCV treatment. We excluded those with HIV, HBV, or previously diagnosed CVD. Incidence rate (per 1, 000 person-years) and risk factors for CVD events (Cox proportional hazards analysis) were determined for various treatment groups. CVD events were identified using ICD-9CM/ICD-10 codes. Kaplan–Meier plots were generated to show and compare CVD-free survival by treatment status and attainment of SVR. Results: Among 32, 575 treated and same number of untreated persons in the final dataset, median age was 58 years, 27% were Black race, and 96% were male. The incidence rate for CVD events/1, 000 person-years (95% CI) among the treated was 19.10 (17.79, 20.50) vs. 32.37 (30.51, 34.33) among the untreated ( P < 0.01). Treatment with a DAA regimen (vs. PEG/RBV; HR [95% CI] 0.68 [0.53, 0.88]) and achieving SVR (HR [95% CI] 0.76 [0.63, 0.92]) were associated with a lower risk of incidence CVD event (table). Kaplan–Meier curves demonstrated that untreated persons had a shorter CVD event-free survival during 30 months of follow-up compared with the treated persons. (figure; log-rank P < 0.0001) Conclusion: HCV treatment is associated with a reduction in incident CVD events. Directly acting antiviral regimens (vs. PEG/RBV) and attainment of SVR (vs. no SVR) are associated with a lower risk of incident CVD events. Disclosures: A. Ajwad Butt, Gilead: Grant Investigator, Research grant.